The effect of demographic factors on academic adjustment among freshmen in Malaysia - Walton Wider; Murnizam Halik; Mazni Mustapha; Ferlis Bahari (2016)
The transition to university is one of the ecological transition in which an individual experience a change in the environment due to the shift of role, location, or both. Looking at the importance of demographic factors to the academic adjustment, the current study aimed to investigate the predictive factor of demographic characteristics of gender, ethnicity, pre-university academic preparation, parental educational level, perceived adult status, and Grade Point Average (GPA) on academic adjustment among freshman in Malaysia. Data were gathered from one of the public universities in East Malaysia namely, Sabah. The findings show that only gender, ethnicity, and perceived adult status show a significant predictor on academic adjustment. Specifically, female students have higher academic achievement than male students; Chinese students have a higher academic achievement than Sabahan Native students; and emerging adult students have a higher academic achievement than self-perceived adult students. Theoretical and practical implications towards academic adjustment literature are further discussed.